PHYTOCHEMICAL ANALYSIS AND IN-VITRO ANTIOXIDANT ACTIVITY OF Xeromphis nilotica STEM-BARK EXTRACT - HG, HAMZA; MUSA M. Y.; DAJA A.; BABABE A.B.; MODU S., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
Free radicals are reactive molecules involved in several physiological processes and have been associated with many ailments such as cancer, arthritis and liver injury that affect a great number of people around the globe. Therefore, there is a need to explore indigenous plant with free radical scavenging activity or antioxidant potentials. Phytochemical analysis as well as estimation of the total phenolic and flavonoid contents of Xeromphis nilotica stem-bark was done using established protocols. Antioxidant and free radical scavenging activity of the extract was assessed by using various in-vitro models. 1,1-Diphenyl-2-picrylhydroxyl (DPPH) quenching assay, hydrogen peroxide scavenging test, total antioxidant capacity using phosphomolybdenum assay were employed and ascorbic acid was used as standard. Alkaloids, carbohydrates, flavonoids, phenolic acids, saponin, steroids, terpenoids and tannins were tested positive however, anthraquinone was not detected. A significant correlation existed between concentrations of the extract and percentage inhibition of free radicals. The extract was also shown to have high total phenolic and total flavonoid contents of 116.32mg GAE/ml and 56.79mg QE/ml respectively. These results clearly indicate that Xeromphis nilotica could be a potential source of natural antioxidant and may possibly be effective against free radical mediated diseases.